Protein interference for regulation of gene expression in plants - A. O. Vyacheslavova; I. A. Abdeeva; E. S. Piruzian; S. A. Bruskin (Вавиловский журнал генетики и селекции)
Transcription factors (TFs) play a central role in the gene regulation associated with a plant's development and its response to the environmental factors. The work of TFs is well regulated at each stage of their activities. TFs usually consist of three protein domains required for DNA binding, dimerization, and transcriptional regulation. Alternative splicing (AS) produces multiple proteins with varying composition of domains. Recent studies have shown that AS of some TF genes form small proteins (small interfering peptide/small interfering protein, siPEP/siPRoT), which lack one or more domains and negatively regulate target TFs by the mechanism of protein interference (peptide interference/protein interference, PEPi/PROTi). The presence of an alternative form for the transcription factor CCA1 of Arabidopsis thaliana, has been shown to be involved in the regulation of the response to cold stress. For the PtFLC protein, one of the isoforms was found, which is formed as a result of alternative splicing and acts as a negative repressor, binding to the full-length TF PtFLC and therefore regulating the development of the Poncirus trifoliata. For A. thaliana, a FLM gene was found forming the FLM-б isoform, which acts as a dominant negative regulator and stimulates the development of the flower formation process due to the formation of a heterodimer with SVP TF. Small interfering peptides and proteins can actively participate in the regulation of gene expression, for example, in situations of stress or at different stages of plant development. Moreover, small interfering peptides and proteins can be used as a tool for fundamental research on the function of genes as well as for applied research for permanent or temporary knockout of genes. In this review, we have demonstrated recent studies related to siPEP/siPROT and their involvement in the response to various stresses, as well as possible ways to obtain small proteins.